"For living room or mantel" - Nelson, George F. (Philadelphia Evening Bulletin, 1969)
"There's unusual decor potential in stuffed chimpanzee and four-foot stuffed alligator (missing one inch of tail), which will be among items up for bid at Academy of Natural Science's Great Auk auction Nov. 14. Checking out chimp are (from left) Mrs. Francis Hopkinson, of Gladwyne; Mrs. Henry Longnecker, of Paoli, and Mrs. Chester Simmons, of Wynnewood." With clipping